Hypoxic-preconditioned mesenchymal stem cell-derived small extracellular vesicles inhibit neuronal death after spinal cord injury by regulating the SIRT1/Nrf2/HO-1 pathway - Rao, Jian; Xie, Haishu; Liang, Zeyan; Yang, Zhelun; Chen, Pingping; Zhou, Maochao; Xu, Xiongjie; Lin, Yike; Lin, Fabin; Wang, Rui; Wang, Chunhua; Chen, Chunmei (Frontiers in Pharmacology, 2024)
Background: Oxidative stress and apoptosis of neurons significantly contribute to the pathophysiological cascade of spinal cord injury (SCI). However, the role of hypoxic-preconditioned mesenchymal stem cell-derived small extracellular vesicles (H-sEVs) in promoting SCI repair remains unclear. Hence, the present study aims to investigate the regulatory effects of H-sEVs on neuronal oxidative stress and apoptotic responses following SCI. Methods: The administration of H-sEVs of SCI rats was assessed using behavioral evaluations such as Basso-Beattie-Bresnahan (BBB) scores, neuroelectrophysiological monitoring, and Catwalk gait analysis. Indices of oxidative stress (including superoxide dismutase [SOD], total antioxidant capacity [T-AOC], and malondialdehyde [MDA]) were measured. Neuronal survival was evaluated through Nissl staining, while the expression level of sirtuin 1 (SIRT1) was examined using immunohistochemical staining. Additionally, histological evaluation of lesion size was performed using hematoxylin-eosin (HE) staining. Tunel cell apoptosis staining and analysis of apoptosis-associated proteins (B-cell lymphoma-2 [Bcl2] and BCL2-Associated X [Bax]) were conducted through immunofluorescence staining and western blot, respectively. Furthermore, the model of oxidative stress was established using PC12 cells, and apoptosis levels were assessed via flow cytometry and western blot analysis. Importantly, to ascertain the critical role of SIRT1, we performed SIRT1 knockout experiments in PC12 cells using lentivirus transfection, followed by western blot. Results: Using those behavioral evaluations, we observed significant functional improvement after H-sEVs treatment. Nissl staining revealed that H-sEVs treatment promoted neuronal survival. Moreover, we found that H-sEVs effectively reduced oxidative stress levels after SCI. HE staining demonstrated that H-sEVs could reduce lesion area. Immunohistochemical analysis revealed that H-sEVs enhanced SIRT1 expression. Furthermore, Tunel cell apoptosis staining and western blot analysis of apoptosis-related proteins confirmed the anti-apoptotic effects of H-sEVs. The PC12 cells were used to further substantiate the neuroprotective properties of H-sEVs by significantly inhibiting neuronal death and attenuating oxidative stress. Remarkably, SIRT1 knockout in PC12 cells reversed the antioxidant stress effects induced by H-sEVs treatment. Additionally, we elucidated the involvement of the downstream Nrf2/HO-1 signaling pathway. Conclusions: Our study provides valuable insights into the effects of H-sEVs on neuronal oxidative stress and apoptosis after SCI. These findings underscore the potential clinical significance of H-sEVs-based therapies for SCI.